Advanced control methodologies of DC-DC converters - He, Yi (2008)
The focus of this thesis is on modeling and control of dc-dc converter. It begins with modeling of Luo converters under steady state using ripple approximate theorem. In addition, a small-signal state-space equation of high-order Luo converter has been derived, which forms the basis for designing a closed loop control system for Luo converters.